Cognitive rehabilitation in a child with Joubert Syndrome: Developmental trends and adaptive changes in a single case report. (December 2015) - Gagliardi, Chiara; Brenna, Viola; Romaniello, Romina; Arrigoni, Filippo; Tavano, Alessandro; Romani, Marta; Valente, Enza Maria; Borgatti, Renato
Highlights: Peaks and valleys characterizes the JS profiles. Genotype/Phenotype relationships are still unclear in JS. Evidence-based rehabilitation in rare syndromes needs a developmental perspective. Intensive focused intervention couples efficacy and ecological approach. Effectiveness of the treatment can be proved beyond the developmental trend. Abstract: We report the clinical and rehabilitative follow up of M, a female child carrying a compound heterozygous pathogenic mutations in the TCTN1 gene and affected by Joubert Syndrome (JS). JS is a congenital cerebellar ataxia characterized by "the molar tooth sign" on axial MRI, a pathognomonic neuroradiological malformation involving the cerebellum and brainstem. JS presents with high phenotypic/cognitive variability, and little is known about cognitive rehabilitation programs. We describe the therapeutic settings, intensive rehabilitation targets and outcome indexes in M's cognitive development. Using a single case evidence-based approach, we attempt to distinguish the effectiveness of the intervention from the overall developmental trend. We assume that an adequate amount of focused, goal directed treatment in a relative short period of time can be at least as effective as one provided in longer time, and much less interfering with the child's everyday life. We conclude by discussing specific issues in cognitive development and rehabilitation in JS and, more broadly, in cerebellar malformations.